2020
DOI: 10.1371/journal.pone.0239800
|View full text |Cite
|
Sign up to set email alerts
|

Global convergence of COVID-19 basic reproduction number and estimation from early-time SIR dynamics

Abstract: The SIR ('susceptible-infectious-recovered') formulation is used to uncover the generic spread mechanisms observed by COVID-19 dynamics globally, especially in the early phases of infectious spread. During this early period, potential controls were not effectively put in place or enforced in many countries. Hence, the early phases of COVID-19 spread in countries where controls were weak offer a unique perspective on the ensemble-behavior of COVID-19 basic reproduction number R o inferred from SIR formulation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 46 publications
7
63
0
Order By: Relevance
“…The investigation of COVID-19 convergence is crucial in the context of India from a readiness perspective as India is unlocking phase-wise to bring its economy back to track. Second, this study complements the [28] study by investigating the convergence based on clustering algorithms. To do so, we use Phillips and Sul (hereafter, PS) [29] techniques that make the clubs based on the COVID-19 cases of states’ speed of convergence.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The investigation of COVID-19 convergence is crucial in the context of India from a readiness perspective as India is unlocking phase-wise to bring its economy back to track. Second, this study complements the [28] study by investigating the convergence based on clustering algorithms. To do so, we use Phillips and Sul (hereafter, PS) [29] techniques that make the clubs based on the COVID-19 cases of states’ speed of convergence.…”
Section: Introductionmentioning
confidence: 86%
“…Few studies also explore the COVID-19 impact on firms/industry/sectors [ 25 , 26 , 27 ]. Moreover, [28] examine the convergence of COVID-19 cases and found that control of the spread among the countries is weak, but a detailed study on COVID-19 convergence at the sub-national level is scanty.…”
Section: Introductionmentioning
confidence: 99%
“…MERS-CoV has a CFR of 34.4%, while, as of 18 November 2020, SARS-CoV is estimated to have a CFR of 2.4% [ 116 , 117 ]. With regard to transmission, SARS-CoV-2 is generally more transmissible than MERS-CoV, with the former estimated to have an overall reproductive number (R0) of 4.5 compared to the latter’s overall R0 of 0.45 in Saudi Arabia [ 117 , 118 , 119 ]. However, it must be noted that the extent of testing ramp-up as well as the role of ’super-spreaders’, i.e.…”
Section: Coronaviruses In the Middle East: Mers-cov And Sars-cov-2mentioning
confidence: 99%
“…However, it must be noted that the extent of testing ramp-up as well as the role of ’super-spreaders’, i.e. individuals who have a "propensity to infect a larger than average number of susceptible individuals", can impact the R0 across different regions [ 119 ].…”
Section: Coronaviruses In the Middle East: Mers-cov And Sars-cov-2mentioning
confidence: 99%
“…There are previous papers to analyze the spread of the pattern of the COVID-19 pandemic. For example, Katul et al ( 3 ) show a significant global convergence in the generic spread mechanisms of the COVID-19. However, the authors focus on the data until early 2020.…”
Section: Introductionmentioning
confidence: 99%